2017
DOI: 10.48550/arxiv.1707.07792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating Lexical and Temporal Signals in Neural Ranking Models for Searching Social Media Streams

Jinfeng Rao,
Hua He,
Haotian Zhang
et al.

Abstract: Time is an important relevance signal when searching streams of social media posts. e distribution of document timestamps from the results of an initial query can be leveraged to infer the distribution of relevant documents, which can then be used to rerank the initial results. Previous experiments have shown that kernel density estimation is a simple yet e ective implementation of this idea. is paper explores an alternative approach to mining temporal signals with recurrent neural networks. Our intuition is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Despite a large body of work on neural ranking models for "traditional" ad hoc retrieval over web pages and newswire documents (Huang et al, 2013;Shen et al, 2014;Guo et al, 2016;Xiong et al, 2017;Mitra et al, 2017;Pang et al, 2017;Dai et al, 2018;McDonald et al, 2018), there has been surprisingly little work (Rao et al, 2017) on applying neural networks to searching short social media posts such as tweets on Twitter. Rao et al (2019) identified short document length, informality of language, and heterogeneous relevance signals as main challenges in relevance modeling, and proposed the first neural model specifically designed to handle these characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a large body of work on neural ranking models for "traditional" ad hoc retrieval over web pages and newswire documents (Huang et al, 2013;Shen et al, 2014;Guo et al, 2016;Xiong et al, 2017;Mitra et al, 2017;Pang et al, 2017;Dai et al, 2018;McDonald et al, 2018), there has been surprisingly little work (Rao et al, 2017) on applying neural networks to searching short social media posts such as tweets on Twitter. Rao et al (2019) identified short document length, informality of language, and heterogeneous relevance signals as main challenges in relevance modeling, and proposed the first neural model specifically designed to handle these characteristics.…”
Section: Introductionmentioning
confidence: 99%